Effect of dates of sowing and nitrogen levels on nutrient uptake (kg/ha), nutrient use efficiency, and quality of Yellow Sarson (Brassica rapa var. trilocularis) grown in rice fallow (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at Assam Agricultural University, Jorhat during the Rabi season of the year 2013-2014 with a view to study the effect of dates of sowing, and nitrogen levels on nutrient uptake, nutrient use efficiency, and quality of Yellow Sarson (Brassica rapa var. trilocularis) grown in rice fallow. The treatments comprised of three different dates of sowing i.e. D1: 25th November, D2: 5th December, and D3: 15th December, and five doses of nitrogen i.e., N0: 0 kg N/ha, N1: 20 kg N/ha, N2: 40 kg N/ha N3: 60 kg N/ha and N4: 80 kg N/ ha. Experimental findings revealed that delay in sowing of the crop from 25th November lead to a significant reduction in the growth, and yield attributing characters that consequently lead to yield reduction. NPK content and uptake in seed and stover also reduced with delay in crop sowing. Oil content, N uptake by seed, and P, K uptake by stover, total K uptake, and nitrogen use efficiency were significant up to 60 kg N/ha. Available N and P content in soil after the harvest of the crop was recorded highest at 80 kg N/ha.